Influence of shadow economy legalization on national security of Ukraine - Kolomoiets, T.; Tsybulnyk, N. Yu.; Цибульник, Н. Ю.; Moroz, O.; Prymachenko, V.; Khashev, V. (Entrepreneurship and Sustainability Issues. – 2021. – Vol. 8, № 3 (March). – P. 420-437, 2021)
Проведений аналіз свідчить про наявність широкого спектру схем та інструментів ухилення від оподаткування, комплексне застосування яких, окрім скорочення фіскальних потоків, спричиняє погіршення економічного середовища та виникнення негативних макроекономічних наслідків. Така ситуація зумовлює необхідність розробки дієвого інструментарію протидії ухиленням від оподаткування, що дає змогу своєчасно виявляти протиправні дії суб’єктів господарювання на всіх стадіях їх виникнення. Розробка цих заходів сприятиме підвищенню рівня фінансової безпеки та посиленню конкурентоспроможності економіки України.

The held analysis indicates about the availability of a wide spectrum of schemes and instruments of tax evasion, complex application of which, apart from reduction of the fiscal flows, causes deterioration of the economic environment and appearance of the negative macroeconomic consequences: distortion of the payment balance, capital outflow from the country, formation of additional pressure on the exchange rate, destructive influence on the formation of differently vectored priorities of the customs and tax policy of the country, and deepening of corruption schemes. In general, these losses are reflected in significant volumes of shortfalls in budget revenues and the ability of public authorities to perform functions and powers assigned to them. Under the condition of accelerated development of the European integration processes, entry to the new markets for sales of goods and services, the analysis and identification of all possible schemes of tax evasion and illegal financial flows formation take an important place in the general state strategy on the country’s development. The availability of a considerable variety of types and forms of the shadow financial transactions implementation requires the implementation of a measures complex, aimed at timely identification and prevention, development of methodological instruments for assessment of the effects from the existence of the shadow sector in the national economy. This situation makes it necessary to develop an efficient instrumentarium on counteraction to tax evasion, making it possible to timely detect illegal actions of the economic entities at all stages of their appearance. The development of these measures will contribute to financial security level improvement and strengthening of competitiveness of the economy of Ukraine.

Проведенный анализ свидетельствует о наличии широкого спектра схем и инструментов уклонения от уплаты налогов, комплексное применение которых, помимо сокращения фискальных потоков, приводит к ухудшению экономической конъюнктуры и возникновению негативных макроэкономических последствий. Такая ситуация обуславливает необходимость разработки эффективного инструментария противодействия уклонению от уплаты налогов, позволяющего своевременно выявлять противоправные действия субъектов хозяйствования на всех стадиях их возникновения. Разработка указанных мер будет способствовать повышению уровня финансовой безопасности и усилению конкурентоспособности экономики Украины.
Keywords: Україна; publikatsii u WoS; Ukraine; shadow economy; legalization; national security; financial security; taxation; тіньова економіка; легалізація; національна безпека; фінансова забезпеченість; оподаткування; Украина; теневая экономика; легализация; национальная безопасность; финансовая безопасность; налогообложение